Intensifying aridity shapes network patterns of soil bacterial communities and geographical distribution of sensitive functional groups in grasslands and farmlands on the Loess Plateau - Jia Wang; Xinyi Guo; Yuru Gao; Kang Zhang; Zhen Yang; Xin Zhao; Jushui Hu; Junyao Deng; Jiaqing Liu; Li Li; Peng Shi; Yanbing Lin; et al. (Applied Soil Ecology, 2026)

Native and non-native phages divergently regulate nitrate-reducing community assembly while similarly affecting nitrate reduction pathway partitioning - Ying Zhu; Ruili Li; Xiaoxue Shen; Siyuan Fan; Mingbang Xu; Shuguang Xie (Applied Soil Ecology, 2026)

Social Arousal and Interspecific Calf Handling by Short‐finned Pilot Whales - Agathe Serres; Mingming Liu; Mingli Lin; Hongri Wang; Xiuqing Hao; Songhai Li (Marine Mammal Science, 2026)

A novel fish interferon-derived antimicrobial peptide with rapid, broad-spectrum bactericidal activity and low toxicity for aquaculture disease control - Jing Xu; Yuanyuan Zhou; Yang Cao; Qinjin Li; Shanhao Ye; Jiali Liang; Ruiyao Xie; Xinhua Chen; Xiang-Yang Zhang (Aquaculture International, 2026)

Targeting Eustachian Tube Microenvironment: Probiotic Surfactant Utilization for Antimicrobial Peptide Secretion to Prevent Otitis Media - Xichu Duan; Yuning Xing; Wenwen Liu; Li Li (Probiotics and Antimicrobial Proteins, 2026)

Annual Variation of Secondary Organic Aerosols from Isoprene, α/β-Pinene, β-Caryophyllene, and Aromatics in Tropical Rainforest Area of Southwest China - Xiao Guo; Yali Liu; Minxia Shen; Weining Qi; Yifan Zhang; Lu Li; Yue Cao; Yingkun Jiang; Qian Wang; Shicong Li; Zhuoer Dong; Wenting Dai; et al. (Aerosol Science and Engineering, 2026)

Cooperation between cellulose-degrading complex microflora and enzymes on improving soil organic carbon turnover and stabilization in the saline-alkali soils - Sainan Gao; Xuelian Liu; Chong Wang; Haoyue Qin; Honghao Cheng; Xueya Liu; Mengli Liu (Applied Soil Ecology, 2026)

Dynamic source apportionment of heavy metals in Bohai Bay sediments using a temporally hierarchical PCA-APCS-HBM model - Qiulian Wang; Long Han; Tong Han; Zhenchao Fu; Zeli Li; Han Ding (Marine Pollution Bulletin, 2026)

Integrated transcriptomic and metabolomic analysis reveals suppression of the intestinal IgT-like mediated immune network in grass carp (Ctenopharyngodon idella) under long-term cold stress - Yian Huo; Ruiqin Hu; Mingli Liu; Xianliang Cai; Yan Zhou; Wanying Zhai; Qianghua Xu (Aquaculture, 2026)

Plants shape soil bacterial community structure via soil pH modulation but show marginal effects on fungal community structure - Xueting Li; Mengli Li; Xinyu Zhu; Fengqun Meng (Applied Soil Ecology, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Sulfur-cycle microorganisms regulate soil aggregate dynamics in saline-alkali soils - He Hu; Jia Cao; Mengli Liu; WenLiang Wu; Chong Wang (Applied Soil Ecology, 2026)

Effects of hummock–hollow microtopography on soil microbial communities and their links to soil carbon cycling in a sedge peatland of the Changbai mountains - Biyu Shi; Ming Wang; Guodong Wang; Xingli Li; Tao Zhang (Applied Soil Ecology, 2026)

Linking fine root and fungal traits to rhizosphere soil multifunctionality in a temperate forest - Dongli Li; Zhenghu Zhou; Ruihan Li; Ying Jin; Chunhua Lv (Applied Soil Ecology, 2026)

Soil microbial functional composition in response to planting pattern shifts and farmland abandonment in mountainous Southwest China - Mengying Li; Yuancui Wang; Keli Li (Applied Soil Ecology, 2026)

Dose-dependent responses of N2O emissions to biodegradable microplastics and warming in contrasting subtropical soils of Southwest China - Fuli Li; Xin Zhang; Di Wu; Zhu Chen; Yuechen Tan; Yifei Wang; Wanping Zhang; Roland Bol (Applied Soil Ecology, 2025)

Divergent responses of soil enzyme kinetics to altered precipitation across steppes with varying historical precipitation - Yaru Chen; Aogui Li; Ziyue Shi; Ziyang Peng; Shiqiang Wan; Lingli Liu; Weixing Liu (Applied Soil Ecology, 2025)

Advances on microbial mechanisms of nitrogen transformation during nitrification and denitrification at soil aggregates scale - Haidi Wang; Zhengjun Cui; Yuhong Gao; Bin Yan; Bing Wu; Yifan Wang; Xingkang Ma; Jing Han; Yali Li (Applied Soil Ecology, 2025)

Long-term green manuring increases phosphorus availability in soil by modifying microbial functional genes and enzyme activities - Xiaodong Chen; Yuan Wang; Bin Guo; Junli Liu; Gaoyang Qiu; Kuzyakov Yakov; Hua Li (Applied Soil Ecology, 2025)

Vermicompost and Azotobacter chroococcum amendment of saline-alkali soil decreases nitrogen loss and increases nitrogen uptake confirmed by ZmNRT1.1B of maize - Siping Li; Chong Wang; Huiying Huang; Lei Zhao; Jia Cao; Mengli Liu (Applied Soil Ecology, 2025)

Metabolism, Function, Molecular Mechanism, and Application of Carotenoids in Coloration of Aquatic Animals - Yongguan Liao; Bo Zhang; Deshou Wang; Dongneng Jiang; Chunhua Zhu; Siping Deng; Huapu Chen; Guangli Li; Hongjuan Shi (Reviews in Aquaculture, 2025)
Among vertebrates, aquatic animals have a wide variety of body color. Yellow and red coloration, an important economic trait of aquatic animals, plays pivotal roles in ornamental value and consumption. Fish possess the most chromatophore types in vertebrates, and carotenoids primarily contribute to erythrophore and xanthophore pigmentation. Carotenoid metabolism and regulation of chromatophore development have long been a focus of selective breeding programs in fish. In crustaceans, carotenoids have been proven to be involved in enhancing coloration. However, the carotenoid requirements vary among different aquatic animals. The metabolic pathways in vivo and biochemical processes have not been well summarized. Thus, in this review, we introduced various types of carotenoids and their metabolic pathways in different aquatic species and described a similar mechanism of ketocarotenoid biosynthesis in fish and birds. We have focused on carotenoid metabolism processes and several significant genes involved in the coloration of vertebrates, such as scavenger receptors, apolipoproteins, ketolases, and β‐carotene oxygenase, and their applications in aquaculture. In addition, we also summarized the current problems of carotenoid addition in diets and emphasized the importance of aquatic breeding and molecular biotechnology in carotenoid coloration and ornamental fish breeding. Finally, we provided our perspectives on fish carotenoid pigmentation research and the aquatic industry. This review will enhance our understanding of fish carotenoid metabolism as well as provide deeper insights into the molecular mechanism of fish muscle and skin pigmentation. It will benefit the production of feed additives and selective breeding for ornamental aquatic animals.

Soil microbes mediate the priming effect in response to 12 years of nitrogen management in different crop cultivation patterns - Kepan Yang; Yali Liu; Shiqiang Ge; Chaoqun Zou; Lei Liu; Xiting Zhang (Applied Soil Ecology, 2025)

Long-term effects of nitrogen fertilization and Bradyrhizobium inoculation on diazotrophic community structure and diversity in soybean cultivation - Wanling Wei; Mingchao Ma; Xin Jiang; Fenliang Fan; Fangang Meng; Fengming Cao; Huijun Chen; Dawei Guan; Li Li; Jun Li (Applied Soil Ecology, 2025)

Profiling of farmland microorganisms in maize and minor-grain crops under extreme drought conditions - Lixin Tian; Mengmeng Han; Kaili Liang; Huihui Liu; Baili Feng (Applied Soil Ecology, 2024)

Regulation of soil phosphorus availability in alpine meadows: Insights from phosphate-mobilising bacteria - Yulin Pu; Shanxin Lang; Yali Li; Ting Li; Shirong Zhang; Xiaoxun Xu; Dagang Yuan; Yongxia Jia; Guiying Wang; Bing Li (Applied Soil Ecology, 2024)

Vaccinium corymbosum interact with mycorrhizal fungi to affect nitrogen metabolism and alleviate soil nutrient limitation - Jing Jiang; Zhiyu Yang; Chunyu Liu; Haifeng Zhu; Huizhi Zhang; Hongyi Yang; Lili Li (Applied Soil Ecology, 2024)

Niche adaptation strategies of comammox Nitrospira in response to nitrogen addition in different types of soil - Wenxin Zou; Shunli Liu; Jian Jiao; Wushuai Zhang; Yuanxue Chen; Prakash Lakshmanan; Ming Lang; Xinping Chen (Applied Soil Ecology, 2024)

Vermicompost enhances the salt tolerance of maize by reshaping the rhizosphere microenvironment - Mengli Liu; Jia Cao; Chong Wang; Binglei Wang; Rui Xue (Applied Soil Ecology, 2024)

Vegetation drives soil microbial metabolic limitation through modifications of soil properties and microbial biomass during desert grassland-shrubland state anthropogenic transition - Zhenjie Zhang; Yanan Zhao; Zhigang Li; Hongmei Wang; Zhili Li; Yanshuo Chen; B. Larry Li (Applied Soil Ecology, 2024)

Kelp breeding in China: Challenges and opportunities for solutions - Zi‐Min Hu; Ti‐Feng Shan; Quan‐Sheng Zhang; Fu‐Li Liu; Alexander Jueterbock; Gaoge Wang; Zhong‐Min Sun; Xiang‐Yu Wang; Wei‐Zhou Chen; Alan T. Critchley; Nai‐Hao Ye (Reviews in Aquaculture, 2024)
Breeding has played an important role in the mariculture and industrialization of kelp in China. However, the current kelp breeding systems in China have encountered some problems relating to germplasm diversity, management, technological innovations, and regional co‐operation. This review summarizes the main challenges, such as top‐down and fragmented management of germplasm libraries, as well as private industry breeding without government regulations, inter‐cultivar accidental admixing and genetic erosion, loss of heterozygosity due to repeated selection and self‐crossing. We outline multiple potential approaches to breed cultivars with improved qualitative/quantitative traits which can be subjected to changing environments, for example: (i) establishing a national germplasm repository to enhance integrative collection and preservation of kelp resources; (ii) planning and implementing kelp breeding programmes according to strategic priorities and goal‐orientations; (iii) optimizing a hybridization‐based breeding pipeline to produce robust cultivars through the introgression of novel alleles and thus the expression of hybrid vigour; (iv) enriching the high‐quality annotated reference genomes and functional analysis of trait‐associated markers/loci to develop DNA‐based breeding technologies; (v) developing new priming‐based (e.g., thermal and disease resistance) bio‐engineering breeding strategies to meet future unpredictable climate change; and (vi) breeding towards an ecological kelp‐microbiome interaction‐based technique to produce cultivars with enhanced performance and adaptability to environmental scenarios. Collectively, the lessons learned from kelp breeding in China and the solutions proposed here may not only potentially improve or re‐invigorate the Chinese kelp industry, but will also assist other developing countries in taking corrective actions to develop a sustainable future kelp farming industry.

A review on the application of chicken immunoglobulin Y in aquaculture - Linpeng Zhang; Li Lin; Zhendong Qin (Reviews in Aquaculture, 2024)
The widespread use of antimicrobial drugs in aquaculture has led to antibiotic residues in aquatic animals. Food safety problems caused by the misuse of antibiotics and antibiotic residues have caused widespread global concern. Consequently, there is an urgent need to develop an alternative to antibiotics for use in aquaculture. Immunoglobulin Y (IgY) has attracted significant attention over recent years because it is readily available, simple to prepare, effective in inhibiting pathogenic microorganisms, free from environmental contamination and free from other toxic side effects. In this paper, we review the research progress relating to the basic structure, physicochemical properties and mechanism of action of IgY. We also highlight the applications of IgY in the control of aquatic animal disease, immunological diagnosis and the preservation of aquaculture products, thus providing a reference for future research and the wider application of IgY in aquaculture.

Numerical investigation of solute migration and release from sediments driven by wave-induced accumulation of pore water pressure - Xiaoli Liu; Shouming Liu; Hongyi Zhao; Dong-Sheng Jeng; Longtao Guo; Tianyuan Zheng (Advances in Water Resources, 2023)

Autophagy regulation of virus infection in aquatic animals - Chen Li; Yunli Zhang; Xianliang Zhao; Li Li; Xianghui Kong (Reviews in Aquaculture, 2023)
Autophagy is a conserved intracellular degradation process that is required to maintain host homeostasis and cope with invading pathogens. Over the past few decades, studies on mammals have greatly increased our understanding of the relationship between autophagy and virus infection. Autophagy may convey the invader to lysosomes to degrade or activate the host immune response against virus replication. However, many viruses have developed some strategies that evade the degradative nature of autophagy or hijack this pathway for their gain. It follows that autophagy during viral infection is a double‐edged sword. In contrast to mammals, the review on autophagy modulated by the aquatic animal virus is limited. Here, after a brief description of the main information about autophagy, we highlight current progress on the interplays between autophagy and virus infection in aquatic animals, including the phenomenon of autophagy upon virus infection, the effect of modulating autophagy on virus replication, and the crosstalk between autophagy and immune response during virus infection. This review will help us better understand the pathogenic mechanism of aquatic animal viruses and develop proper antiviral countermeasures aimed at modulating autophagy.

Positive response of maize husk traits for improving heat tolerance during flowering by alleviating husk inside temperature - Yuanyuan Wang; Dechang Sheng; Xinfang Hou; Ping Zhang; Xiaoli Liu; Pu Wang; Shoubing Huang (Agricultural and Forest Meteorology, 2023)

Bidirectional reflectance factor measurement of conifer needles with microscopic spectroscopy imaging - Yongkang Lai; Xihan Mu; Yuequn Bian; Xiaohan Dong; Feng Qiu; Xinyu Bo; Zhixiang Zhang; Yi Li; Xinli Liu; Linyuan Li; Donghui Xie; Guangjian Yan (Agricultural and Forest Meteorology, 2023)

The role of ferroptosis in fish inflammation - Feng Gao; Xiaowei Shi; Chao Pei; Xianliang Zhao; Lei Zhu; Jie Zhang; Li Li; Chen Li; Xianghui Kong (Reviews in Aquaculture, 2023)
Ferroptosis, as one of cell death modalities, is driven by iron‐dependent phospholipid peroxidation and regulated by various cellular metabolic pathways, including iron, amino acid and lipid metabolism, as well as disease‐related signalling pathways. Cell survival or death is a critical issue in the inflammatory response. On the one hand, ferroptosis is more immunogenic than apoptosis, and ruptured ferroptotic cells release damage‐associated molecular patterns (DAMPs), which can trigger an inflammatory response. On the other hand, various pathogenic bacteria may cause peroxidation of polyunsaturated fatty acids (PUFAs) on the cell membrane, leading to ferroptosis. In fish, the key genes and signalling pathways related to ferroptosis are conserved, but there are still differences among fish species. In recent years, frequent occurrences of fish diseases have posed a considerable challenge to the large‐scale aquaculture. The specific precursors for ferroptotic cell death were iron‐dependent oxidative stress and lipid peroxidation, which always occur in fish inflammation. This review summarizes recent studies on ferroptosis in fish inflammation, that is, iron‐dependent programmed cell death, to address ferroptosis, inflammation and correlations between them in fish. This review may contribute to a better understanding of the underlying mechanisms of ferroptosis and inflammation in fish and provides suggestions for sustainable development and large‐scale aquaculture farming.

Current progress in the authentication of fishery and aquatic products using multi‐element and stable isotope analyses combined with chemometrics - Cui Han; Li Li; Xuan Dong; Qinfeng Gao; Shuanglin Dong (Reviews in Aquaculture, 2022)
Fraud occurs frequently in the fishery and aquatic product markets. Therefore, the authentication of fishery and aquatic products has become a crucial issue. Recently, elemental and stable isotope analyses have become popular for aquatic food authentication. In this review, relevant literature was collected to highlight the current progress in the authentication of fishery and aquatic products using multi‐element and stable isotope analyses combined with chemometrics. Both technologies provide valuable insight regarding geographic origin, culture method, and species identification of fishery and aquatic products. Their classification rate varied from 60% to 100% in most studies. The formation of both elemental and stable isotope profiles of fishery and aquatic products is complex and affected by many factors, including diet, biological differences, and culture environment. The classification rate of these methods may be increased by combining multiple technologies, selecting the correct elements and stable isotopes for specific purposes, selecting and verifying proper discrimination methods, and increasing sample sizes. This review provides valuable information to build reliable and stable tracing methods for fishery and aquatic products.

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

Sustainable aquaculture development: a review on the roles of cloud computing, internet of things and artificial intelligence (CIA) - Umar Farouk Mustapha; Abdul‐Wadud Alhassan; Dong‐Neng Jiang; Guang‐Li Li (Reviews in Aquaculture, 2021)
Each year, there is a significant rise in demand for global food production due to population increase and a rise in demand for protein food sources. This puts pressure on capture fishery as fish is a preferred protein source worldwide. However, the more resources we put into the capture fisheries to obtain maximum catch, the faster the fisheries stock becomes depleted. The best option left to produce enough fish to meet demand is relying on advanced aquaculture. Unfortunately, the impact of technological advancement in the aquaculture sector is not profound compared to the agricultural and manufacturing sectors. The advent of Cloud computing, Internet of Things, and Artificial Intelligence (CIA) has expanded numerous possibilities for applying and integrating information technology in all works of life. This article reviews the emergence of research development on CIA and the potential to revolutionize the aquaculture industry. The use of CIA techniques and tools such as drones, nano and micro‐sensors, bionic robots, remote cameras, intelligent sorting, energy‐saving processing equipment, statistical modules, and algorithms will reduce human intervention and increase aquaculture productivity. Also, the application of CIA in the aquaculture value chain to ensure effectiveness in traceability, feeding, disease detection, growth prediction, environmental monitoring, market information, and others is key to increasing aquaculture productivity and sustainability. Therefore, the future of aquaculture operations with less human labour, effective maintenance, and resource utilization largely depend on innovative technologies. Here, we outlined the need for adopting innovative technologies and the limiting factors that hinge on CIA adoption in the aquaculture industry.

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image